1969
DOI: 10.1037/h0082690
|View full text |Cite
|
Sign up to set email alerts
|

Draw-a-Man and Raven's Progressive Matrices (1938) intelligence test performance of reserve Indian children.

Abstract: Eighty-six Canadian reserve Indian children, from 7 to 15 years of age, were tested on the Harris-Goodenough Draw-a-Man and Raven's Progressive Matrices (1938) tests. The Draw-a-Man mean IQS were: girls 100, boys 113; a significant difference. The Raven mean IQS were: girls 79, boys 85; not significantly different. The tests were significantly correlated (raw scores, r = 0.67; IQS, r = 0.53). Older children had significantly lower IQS on the Raven only. These results caution against assuming that these tests, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

1970
1970
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
1
2
0
1
Order By: Relevance
“…The descriptive analysis showed that GHDT average IQ score for girls is higher than for boys, from both raters. This is in line with the results obtained by the previous research where GHDT average IQ score for girls is higher than boys [8,27,28]. It is also said that most Human Figure Drawing researchers such as Goodenough, Koppitz, Harris, and Machover found that the drawings of girls in the primary grades are superior to those of boys [29].…”
Section: Discussionsupporting
confidence: 90%
“…The descriptive analysis showed that GHDT average IQ score for girls is higher than for boys, from both raters. This is in line with the results obtained by the previous research where GHDT average IQ score for girls is higher than boys [8,27,28]. It is also said that most Human Figure Drawing researchers such as Goodenough, Koppitz, Harris, and Machover found that the drawings of girls in the primary grades are superior to those of boys [29].…”
Section: Discussionsupporting
confidence: 90%
“…For the Man scale, 33 boy-girl raw score comparisons with tests of significance were reported in nine studies of noninstitutionalized American children (Coyle, Glance, & Joesting, 1977;Harris & Finder, 1974;Harris et al, 1970;Henderson, Fay, Lindemann, & Clarkson, 1973;Laosa, Swartz, & Holtzman, 1973;McCormick & Schnobrick, 1971;O'Keefe, Leskosky, O'Brien, Yater, & Barclay, 1971;Olivier & Barclay, 1967;Wiltshire & Gray, 1969). No significant differences in the drawing ability of the sexes were reported in 24 of the 33 comparisons across ages 3 to 18.…”
Section: Sex Differencesmentioning
confidence: 99%
“…Only one study was found that warned against the use of the Raven's test. Wiltshire and Gray (1969) reported that Canadian Cree Indians scored considerably lower than the Raven's norms. The authors concluded that the performance of the Cree could not be directly evaluated from the test's published norms.…”
Section: Instrumentmentioning
confidence: 89%